“How Worldly Should We Get to Win the World?”: Autoethnographic Reflections on Sacred and Mundane Entanglements in Nigerian Gospel Music Discourse - AJOSE, Toyin Samuel (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This article explores the intersection of religion and popular culture by examining how the connections between the sacred and secular are portrayed in public discourse surrounding Nigerian gospel music. Studies exploring gospel music in Nigeria have examined its growth, style, classifications, and significance in facilitating spirituality in everyday life. As a form of Christian popular culture, gospel music influences and is influenced by secular art forms. This interaction has generated several criticisms from both within and outside the Christian fold. Despite the longstanding tensions relating to the entanglement between gospel music and secular popular expressions, how these controversies are encountered, framed, and discussed in public discourse has not received scholarly investigation. Based on years of observation and sacred public conversations, including sermons and social media comments, this study aims to answer the following question: How are the concepts of spirituality and ‘worldliness’ framed in the public discourse on gospel music practices in Nigeria? What are the possible explanations for the interaction between the sacred and the secular in Nigerian gospel music? What do these public discourses mean for understanding how the ‘boundaries’ of Christianity and its artistic forms, including gospel music, are stretched, collapsed, constructed, reconstructed, mediated, and negotiated through the structures of popular culture in Nigeria? The study reveals that symbolic entanglements, fandom and celebrity culture, as well as labour and religious economy, frame the discourse regarding the perpetual interactions between gospel music and secular entertainment. It concludes that the public controversies regarding the extent to which religious actors, including preachers and gospel musicians in Nigeria and Africa, will go (including mobilising secular popular culture) to win the world are limitless.